Development of Draping Illustrative Video Media Tutorials in the Draping Course in the IKK Department, FPP, UNP - Hasanah, Nuratiyah Rina Gustina; Sri Zulfia Novrita; Yusmerita; Puji Hujria Suci (Universitas Muhammadiyah Enrekang, 2026)
This study developed a learning video for the Draping course as a solution to the problem of learning media that is still limited to jobsheets, students' difficulties in understanding jobsheets without clear visuals, limited lecture hours, and students also still experience difficulties in making Draping illustrations in the Draping course. This study aims to produce a learning video media tutorial Draping illustrations and describe its validity and practicality for Fashion Design students of the Department of IKK FPP UNP. This study uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop), without the Disseminate stage. The research subjects validator consisted of four experts, namely 2 media experts and 2 material experts, lecturers teaching praktikalita the Draping course, 10 students praktikalitas in small group trials, and 30 students praktikalitas in large group trials. The instrument was a validation and practicality questionnaire with a Likert scale assessment. The results of the media validation obtained a score of 94% and 90% for material experts, with an average of 92% in the very valid category. The practicality test for the lecturer reached 91%, the small group 87%, and the large group 89%, with an average of 90% in the very practical category. Thus, this video learning medium is declared very valid, very practical, and suitable for use in Draping lectures.